Beckman Enzyme Activity Analyzer System TR (1973)
Beckman’s System TR, introduced in 1973, was the first automated analyzer for clinical enzymes.
Keywords: Medical laboratories--Equipment and supplies; Scientific apparatus and instruments; Enzymes--Analysis; Beckman Instruments, Inc.; Medical instruments and apparatus